Cytotoxic Activity of Extracts and Sesquiterpene Lactones from Stachycephalum argentinum - Alarcon, R. (2000)
The extracts and sesquiterpene lactones of S.argentinum were assayed to deter- mine their biological activity on Artemia salina. The most active compound was costunolide (1) with LD50 = 62 ppm.